Enhancing sidewalk accessibility assessment for wheelchair users: An adaptive weighting fuzzy-based approach - Maryam Naghdizadegan Jahromi; Najmeh Neysani Samany; Meysam Argany; Mir Abolfazl Mostafavi (Heliyon)
To reach a destination within the community, it is crucial that wheelchair users possess the ability to plan, execute, and acquire knowledge of routes in a safe and efficient manner. While numerous methods have been introduced for assessing the accessibility of sidewalks, existing studies often overlook the variations in the perception of the accessibility of long segments based on each wheelchair user's capabilities. Extended distances may lead to increased fatigue, impacting the ability of individuals with mobility disabilities to navigate sidewalks comfortably and independently. In this paper, we propose an adaptive weighting method, effectively addressing the accessibility assessment of sidewalks by considering more specifically the impact of sidewalk length. The results underscore the significant impact of sidewalk length on mobility, delineating varying accessibility indices in long sidewalk segments, and offering a more realistic evaluation of accessibility based on wheelchair users' perceptions. For validation purposes, the proposed model was implemented in a personalized routing tool called MobiliSIG and compared with the conventional fuzzy model provided by the tool for accessibility assessment through a case study in Quebec City. The results demonstrated improved routing outcomes compared to previous methods, showcasing the effectiveness of our model in enhancing sidewalk accessibility assessment.